EFEKTIFITAS MODIFIKASI MODERN DRESSING DAN TERAPI OZON TERHADAP PENYEMBUHAN LUKA PADA PASIEN DENGAN PRESSURE ULCER DI WOCARE CLINIC BOGOR - FATMAWATI, ISTIADAH; Subiyanto, AA; J, HERMANU (HOSPITAL MAJAPAHIT (JURNAL ILMIAH KESEHATAN POLITEKNIK KESEHATAN MAJAPAHIT), 2015)
Playing is the demands and needs of the child. By playing, child's can satisfy the demands and needs of child development in cognitive and motoric dimension, creativity, emotional language of social values and attitudes. Through playing children will learn to control himself, understand life, understand their world. Stimulation is an activity to stimulate basic ability by the environment (mother, father, nannies and other family members) to optimize growth. The method used is descriptive qualitative research. The strategy used is a case study of a single fixed. Study means a single case study was only performed on one target, namely the location of TK Muslimat Sentul Kecamatan Tanggulangin Kabupaten Sidoarjo with one characteristic that is about the modeling game. Research results show that the purpose of playing preschoolers include encouraging imagination / creativity of children, optimize the growth of all organs, to socialize with others, develop intellectual abilities. Preparation of the teachers is very important support in the implementation of child development tests. Preparation of equipment and a place to be used in the test development must be adapted to the situation of children. So that a teacher must have careful planning and clear. Implementation of development tests conducted in accordance benchmark in the process of learning in early childhood. The positive impact encountered was a child can play while learning and honing the brain for the correct selection of games can be challenging for children to play with a maximum of sharpening their brains. The conclusion of this study is that the execution of the test execution progress for children in TK Muslimat Sentul Kecamatan Tanggulangin Kabupaten Sidoarjo is going well and smoothly in accordance with the established plan.Keyword : Perception, Parent, Playing, Modelling